2015
DOI: 10.1371/journal.pone.0115997
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Oligodendrocyte Progenitor Cell Transplantation in Premature Rat Brain following Hypoxic-Ischemic Injury

Abstract: Periventricular leukomalacia (PVL) is a common ischemic brain injury in premature infants for which there is no effective treatment. The objective of this study was to determine whether transplanted mouse oligodendrocyte progenitor cells (OPCs) have neuroprotective effects in a rat model of PVL. Hypoxia-ischemia (HI) was induced in 3-day-old rat pups by left carotid artery ligation, followed by exposure to 6% oxygen for 2.5 h. Animals were assigned to OPC transplantation or sham control groups and injected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…Neonatal hypoxic-ischemic brain damage (HIBD) is a relatively common malignant complication caused by clinical perinatal asphyxia in infants and young children (Chen et al, 2015;Thatipamula et al, 2015), which occurs in 1 to 6 of every 1,000 live term births (Gu et al, 2016;Koonrungsesomboon et al, 2014). Statistics suggests that approximately 40% of the affected infants die in the neonatal period and an additional 30% have lifelong neurological deficits including cerebral palsy, epilepsy and cognitive disabilities (Hristova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal hypoxic-ischemic brain damage (HIBD) is a relatively common malignant complication caused by clinical perinatal asphyxia in infants and young children (Chen et al, 2015;Thatipamula et al, 2015), which occurs in 1 to 6 of every 1,000 live term births (Gu et al, 2016;Koonrungsesomboon et al, 2014). Statistics suggests that approximately 40% of the affected infants die in the neonatal period and an additional 30% have lifelong neurological deficits including cerebral palsy, epilepsy and cognitive disabilities (Hristova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pathological accumulation of excessive reactive oxygen species (ROS) and subsequent oxidative stress results in brain necrosis and apoptosis (Chang et al, 2016). Endogenous antioxidants such as superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), possess the ability of scavenging overproduction of oxidants to prevent deleterious ROS generation (Chen et al, 2015;Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to protecting OLGs from damage, increasing remyelination by transplanting OPCs [38,39] is also a potential strategy for ischemic stroke treatment. Substances such as growth factors, cytokines, and chemokines activate OPCs and induce remyelination after stroke [6,40].…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell (SCs) technology is considered to be a new promising tool for the effective treatment of CNS disorders [5,6]. Numerous studies have demonstrated that SCs transplantated into the site of injury favored the recovery of damaged tissue via differentiation into specific cell type and production of the biomodulators (growth factors, cytokines and immunomodulators) essential for cell survival, reduction of inflammation and maintenance of tissue homeostasis [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…MMSCs not only have a tropism for the injured zone in the brain but also show strong immunomodulatory potential suppressing inflammation and favoring recovery of function [10]. Such promising neuroprotective effect from MMSCs transplantation was shown, particularly, in PVL animal model [6,11]. However, it remains unclear if this positive effect is mediated by actual presence MMSCs in the tissue or by distant modulation via released bioactive factors.…”
Section: Introductionmentioning
confidence: 99%